The Salem witchcraft and the origin of the north American plea bargaining: contrasting the dichotomous knowledge of the criminal justice systems - Sarah Ribeiro; Rodrigo Régnier Chemim Guimarães (Revista Brasileira de Direito Processual Penal, 2020)
The question that drives this article is: can the North American plea bargaining originate by means considered by contemporary doctrine as predominantly "inquisitorial"? If so, and considering that 95% of the cases in that country are resolved by plea bargaining, does it make sense to continue saying that the criminal procedure system in the United States of America is "adversarial"? And more: deconstructed the labels that predominate in the doctrine around this theme, does it make sense to insist on the use of the dichotomy of criminal procedural systems, in adversarial versus inquisitorial, notably in the discussion of the adoption of procedural models inspired by the American plea bargaining? These questions are intended to be answered based on the historical reconstruction of plea bargaining in the United States, which goes back to its Puritan colonization, its attachment to economic disputes and the practices introduced in the 17th century, whose primitive expression is found in the famous judgment of the “witches of Salem” in Massachusetts. The article then explores how things went in this case, identifying the similarity between the methods used in the Salem witches' trial and the modern plea bargaining. Physical and psychological torture, linked to the possibility of harsh penalties, which frightened those accused of heresy in the processes of the medieval inquisition, as well as their limited possibility of defense, were also found in the Salem witch trials. Thus, what can be seen is that a criminal justice model perpetuated as "inquisitorial" by cultural transmission has been perpetuated, as a medieval heritage in parts of the North American criminal process. This shows that there is no conceptual rigidity about criminal procedural systems, contradicting a significant part of contemporary doctrine that continues to cling to the inquisitorial versus adversarial dichotomy. And it allows us to move forward, detaching ourselves from this doctrinal dichotomous tie, which is typical of the pretensions of scientific organization of the 19th century in Europe, and which has since promoted a dualist vision and which does not accept to see anything beyond the antagonistic labels of inquisitorial or adversarial, to inquire whether it is convenient or not and in what terms, in light of the 1988 Constitution, to adopt models inspired by the American bargaining model in Brazil.